2007
DOI: 10.1158/0008-5472.can-06-4274
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Inhibitor PS-341 (Bortezomib) Up-Regulates DR5 Expression Leading to Induction of Apoptosis and Enhancement of TRAIL-Induced Apoptosis Despite Up-Regulation of c-FLIP and Survivin Expression in Human NSCLC Cells

Abstract: The proteasome inhibitor PS-341 (bortezomib or Velcade), an approved drug for treatment of patients with multiple myeloma, is currently being tested in clinical trials against various malignancies, including lung cancer. Preclinical studies have shown that PS-341 induces apoptosis and enhances tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis in human cancer cells with undefined mechanisms. In the present study, we show that PS-341 induced caspase-8-dependent apoptosis, cooperat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
137
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(160 citation statements)
references
References 44 publications
21
137
2
Order By: Relevance
“…However, the advantage of soluble inhibitors is that their delivery would be easier and more efficient than gene transfer. Small molecules that inhibit IKK activity have indeed been described, and some of these molecules have been shown to induce apoptosis in cancer cells (19)(20)(21)(31)(32)(33). However, compounds that inhibit IKK with very high affinities have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, the advantage of soluble inhibitors is that their delivery would be easier and more efficient than gene transfer. Small molecules that inhibit IKK activity have indeed been described, and some of these molecules have been shown to induce apoptosis in cancer cells (19)(20)(21)(31)(32)(33). However, compounds that inhibit IKK with very high affinities have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the limitations of TRAIL-induced cytotoxicity, the combination of TRAIL with other small molecule compounds has been postulated as strategy to potentiate the cytotoxicity of TRAIL and its therapeutic applications. Indeed, it was reported that several chemotherapeutic agents and natural products, such as CDDP, 10 etoposide, 10,11 doxorubicin, 12 PS-341 (bortezomib), 13 tunicamycin, 14 rottlerin, 15 brandisianins, 16 silibinin 17 and sodium butyrate, 18 were succeeded to cause the sensitization of TRAIL-resistant tumor cells to TRAIL-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Up-regulation of proapoptotic Noxa is frequently observed in bortezomib-treated cells and has been shown to mediate apoptosis induction by this agent in cell lines representing multiple myeloma (16,17), non-small cell lung cancer (18), mantle cell lymphoma (19,20), and melanoma (17). Moreover, the ability of bortezomib to sensitize non-small cell lung cancer, myeloid leukemia, and renal carcinoma cells to tumor necrosis factor -related apoptosis-inducing ligand is associated with up-regulation of the DR5 death receptor and down-regulation of c-FLIP (21,22), whereas tumor necrosis factor -related apoptosis-inducing ligand sensitization of prostate and colon cancer cells has been reported to involve Bik and Bim (23 -25).…”
Section: Introductionmentioning
confidence: 99%